Research on the lubrication characteristics of harmonic gear transmission meshing areas - Xu, Xiangyang (Strojniški vestnik, 2020)
To analyse the lubrication characteristics of harmonic gears and lay the foundation for the study of its gear tooth failure performance and dynamic characteristics, based on the tooth contact geometry of harmonic gear, the integrated curvature radius, tooth load, and entrainment velocity at the meshing point of the gear teeth in the harmonic gear transmission are analysed. A finite-length line contact elastohydrodynamic lubrication (EHL) model for harmonic gears is established. The numerical calculation method is used to solve the oil film thickness and pressure distribution in the lubricating area, and the effects of rotational speed and temperature on the contacting load ratio and film thickness ratio of the meshing area are studied, as well as the change of oil film stiffness under different working conditions. The results show that along the meshing direction, the pressure is small at the end and reaches a peak at the centre, and the film thickness is the largest in the entrance area and is evenly distributed in the centre contact area. As the speed increases, the gear tooth contact load ratio decreases, the oil film thickness ratio increases, the stiffness of the oil film decreases significantly, and the lubrication effect is improved; but the temperature has the opposite effect. Proper increase of rotation speed and decrease of oil temperature can effectively improve the lubrication characteristics of the system.
Keywords: delovni pogoji; elastohidrodinamično mazanje; elastohydrodynamic lubrication; harmonic gear transmission; harmonični zobniški prenosnik; lastnosti mazanja; lubrication characteristics; meshing area; numerične metode; področje ubiranja